(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This study examines media attention to innovation in journalism education, focusing on how national and international media outlets frame curricular reforms, technological integration, and pedagogical changes. Using a combination of content analysis, discourse analysis, case studies, and comparative media review, the research identifies dominant narratives, evaluative strategies, and thematic priorities in media reporting.